2010
DOI: 10.1371/journal.pone.0015623
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol Delivery of Small Hairpin Osteopontin Blocks Pulmonary Metastasis of Breast Cancer in Mice

Abstract: BackgroundMetastasis to the lung may be the final step in the breast cancer-related morbidity. Conventional therapies such as chemotherapy and surgery are somewhat successful, however, metastasis-related breast cancer morbidity remains high. Thus, a novel approach to prevent breast tumor metastasis is needed.Methodology/Principal FindingAerosol of lentivirus-based small hairpin osteopontin was delivered into mice with breast cancer twice a week for 1 or 2 months using a nose-only inhalation system. The effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 42 publications
(44 reference statements)
0
10
0
Order By: Relevance
“…11 , 50 - 52 OPN inhibition decreases local breast cancer growth and metastasis. 17 , 28 , 29 , 53 - 55 Therefore, OPN has been proposed as an anti-cancer target. Studies suggest that OPN-integrin binding via the RGD domain stimulates tumor cell invasiveness and migration, in part through activation of MMPs/uPA.…”
Section: Discussionmentioning
confidence: 99%
“…11 , 50 - 52 OPN inhibition decreases local breast cancer growth and metastasis. 17 , 28 , 29 , 53 - 55 Therefore, OPN has been proposed as an anti-cancer target. Studies suggest that OPN-integrin binding via the RGD domain stimulates tumor cell invasiveness and migration, in part through activation of MMPs/uPA.…”
Section: Discussionmentioning
confidence: 99%
“…al. used an orthotopic mouse breast cancer model that metastasized to the lungs (98). Two weeks after tumor inoculation, shRNA against OPN was delivered as an aerosol into the lungs of the mice.…”
Section: Introductionmentioning
confidence: 99%
“…It can be used in patients with cardiac, cerebral or peripheral vascular diseases, as well as kidney, liver or lung diseases. In fact, our research group has demonstrated that aerosol delivery of therapeutic genes/molecules has excellent and sustained effects on lung tumorigenesis [14,15,16,17,18]. Therefore, aerosol delivery of DHE could provide a novel approach with the potential for use in lung cancer, and this study is currently under way.…”
Section: Discussionmentioning
confidence: 99%